Plant genetic variation drives geographic differences in atmosphere–plant–ecosystem feedbacks - Shannon L. J. Bayliss (Wiley, 2020)
Why this research Matters The objective of this study was to understand how genetic variation in a riparian species, Populus angustifolia, affects mass and energy exchange between the land and atmosphere across ~1,700 km of latitude of the western United States. To examine the potential for large‐scale land–atmosphere feedbacks in hydrologic processes driven by geographic differences in plant population traits, we use a physical hydrology model, paired field, and greenhouse observations of plant traits, and stable isotope compositions of soil, stem, and leaf water of P. angustifolia populations. Populations show patterns of local adaptation in traits related to landscape hydrologic functioning—a 47% difference in stomatal density in greenhouse conditions and a 74% difference in stomatal ratio in the field. Trait and stable isotope differences reveal that populations use water differently which is related to historical landscape hydrologic functioning (evapotranspiration and streamflow). Overall, results suggest that populations from landscapes with different hydrologic histories will differ in their ability to maintain favorable water balance with changing atmospheric demands for water, with ecosystem consequences.